2022
DOI: 10.1155/2022/4362317
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture May Inhibit Oxidative Stress of Premature Ovarian Failure Mice by Regulating Intestinal Microbiota

Abstract: Premature ovarian failure (POF) is the leading cause of female infertility, and there is no optimal treatment or medication available currently. For POF, electroacupuncture (EA) has been considered a promising therapeutic approach, but the mechanism for this is not clear. In this study, we explored the effects of EA (CV4, ST36, and SP6) on oxidative stress and intestinal microbiota of high-fat and high-sugar- (HFHS-) induced POF mice. The development of mice follicles was observed by hematoxylin and eosin (HE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Ferroptosis has been acknowledged to take part in the pathogenesis of many diseases such as cancers [ 36 – 38 ] and neurodegenerative diseases [ 39 , 40 ], but there are few reports in the field of POF. Geng et al reported electroacupuncture can efficiently suppress ovarian oxidative stress and Fe 2+ accumulation in POF mice, which offers a possibility that ferroptosis may be linked to POF [ 17 ]. There are even more straightforward experiments to state ferroptosis is associated with chemotherapy-induced POF.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis has been acknowledged to take part in the pathogenesis of many diseases such as cancers [ 36 – 38 ] and neurodegenerative diseases [ 39 , 40 ], but there are few reports in the field of POF. Geng et al reported electroacupuncture can efficiently suppress ovarian oxidative stress and Fe 2+ accumulation in POF mice, which offers a possibility that ferroptosis may be linked to POF [ 17 ]. There are even more straightforward experiments to state ferroptosis is associated with chemotherapy-induced POF.…”
Section: Discussionmentioning
confidence: 99%
“…The main bacteria involved in the production of IPA include L. reuteri 47 and Clostridium genus 48 , while the major IAA-producing bacteria are Bacteroides, Clostridium and Bifidobacterium genus 49 . Both previous animal experiments and clinical studies have demonstrated that abnormal ovarian function such as premature ovarian failure (POF) and polycystic ovarian syndrome (PCOS) can alter the composition of the intestinal flora compared to controls with normal ovarian function 50 , 51 . With this in mind, we hypothesized that ovarian senescence may lead to a decrease in the intestinal flora that degrades indole metabolites, which in turn reduces the levels of indole metabolites such as IPA, and IAA in the FF and thus diminishes the protective effect on the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Interventions such as electroacupuncture and resveratrol have demonstrated potential in mitigating ovarian oxidative stress and inflammation by regulating the gut microbiota. 42,43 Furthermore, acetate, a short-chain fatty acid (SCFA), has been shown to alleviate ovarian inflammation in type 2 diabetic (T2D) and PCOS rats by reducing malondialdehyde (MDA) and tumor necrosis factor-α (TNF-α) levels, increasing glutathione, and restoring ovarian steroid secretion. 55,56 Both in vitro and in vivo experiments using pigs and rats have revealed that medium-and short-chain fatty acids (MSFAs) enhance the expression of key genes involved in ovarian steroidogenesis and granulosa cell luteinisation.…”
Section: Food and Function Reviewmentioning
confidence: 99%